Incremental Value of Sestamibi SPECT/CT Over Dual-Phase Planar Scintigraphy in Patients With Primary Hyperparathyroidism and Inconclusive Ultrasound - Assante, Roberta; Zampella, Emilia; Nicolai, Emanuele; Acampa, Wanda; Vergara, Emilia; Nappi, Carmela; Gaudieri, Valeria; Fiumara, Giovanni; Klain, Michele; Petretta, Mario; Cuocolo, Alberto (Frontiers in Medicine, 2019)
Background: We evaluated the incremental value of 99mTc-sestamibi single photon-emission computed tomography (SPECT)/computed tomography (CT) over planar imaging for localization of abnormal parathyroid tissue in patients with primary hyperparathyroidism. Methods: Forty-six patients with biochemical evidence of hyperparathyroidism and inconclusive ultrasound underwent 99mTc-sestamibi dual-phase planar scintigraphy and SPECT/CT for preoperative localization of parathyroid adenoma. Imaging findings were compared with histopathological data. Recursive partitioning and regression trees (RPART) analysis was used to assess the value of SPECT/CT over planar scintigraphy for classifying patients with or without adenoma. The added value of SPECT/CT was also evaluated by decision curve analysis. Results: Planar scintigraphy was positive for presence of hyperfunctioning parathyroid in 52% of patients, with sensitivity of 63% and specificity of 100%. SPECT/CT was positive in 80% of patients with sensitivity of 97% and specificity of 100%. At RPART analysis, after an initial split on planar imaging results, no further split was performed in patients with positive results, while those with negative results were further stratified by SPECT/CT. At decision curve analysis, the model including SPECT/CT was associated with the highest net benefit compared to the model including only planar technique and to a strategy considering that all patients should be treated. Conclusion: 99mTc-sestamibi SPECT/CT provides incremental value over dual-phase scintigraphy in preoperative localization of hyperfunctioning parathyroid tissue in subjects with inconclusive ultrasound. Hybrid technique allows a better identification of pathological lesion to perform minimally invasive surgery and showed the highest net benefit, improving selection of surgical approach